Green Cayenne Pepper Production and Marketing Collaboration to Increase Farmer’s Income In East Lombok Regency West Nusa Tenggara - Bulu, Yohanes Gili; Sari, Ika Novita; Utami, Syvia Kusumaputri; Adnyana, I Putu Cakra Putra (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 2 (2020): Vol.14.No 2, 2020DO - 10.24843/SOCA.2020.v14.i02.p05, 2020)
This study aimed to know: (1) the form of the collaboration done on the green cayenne pepper production and marketing between the farmer and the distributor (2) to analyze the farmer income on the green cayenne pepper production and marketing collaboration. This study was conducted in the central of the cayenne pepper production in East Lombok Regency in March 2017-March 2018. The survey method was employed in this study. The population and participants joined in this study were chosen by the purposive sampling technique. The descriptive analysis was done to merge the quantitative and qualitative analyses used in this study. Results showed that the cayenne pepper production and marketing between the farmer and distributor were productive and able to strengthen their social capital. Technological devices used were also effective in increasing the production of the cayenne pepper as much as IDR 11,343 IDR kg/ha. The farmer gross income mean was reaching IDR 243,210,000/ha, while the mean of the production cost was IDR 80,040,000/ha, therefore the net income was IDR 163/170,000/ha. The cayenne pepper marketing between the distributors in the West Nusa Tenggara and some regencies in Indonesia was done based on trust and some social norms agreed.